Pemilihan Jenis Kapal Perang Guna Menghadapi Ancaman di Laut Natuna Dengan Analytical Hierarchy Process (AHP) - Marno Arbhyanto (AGUSPATI Research Institute, 2023)
the current issue in the North Natuna Sea carries potential and factual threats that will directly impact the stability, security, and sovereignty of Indonesia's territory. This requires a high level of combat readiness from the components of the Indonesian Navy, including both the equipment and personnel preparedness, as well as the formulated system in the Integrated Fleet Weapon System (Sistem Senjata Armada Terpadu or SSAT). This research will discuss the selection of warship types and warship criteria in order to prepare for facing these threats. The method used in this analysis is the Analytical Hierarchy Process (AHP) method, which combines warship criteria and types. Based on this method, the warship that can support and meet the criteria needed to face threats in the Natuna Sea is the Arrowhead Class ship from the United Kingdom, with a weight value of 5.530481383